Alocação de pessoas em projetos de software utilizando sistemas multiagentes - Cafarate, Liane Santiago (2011)
The tasks allocation process is a key activity in project management. Being able to conciliate the people profile, as well their professional aspirations is a real challenge for managers. Software projects differ from the rest because of its intangibility and complexity, characteristics that contribute to the failure of these projects. In addition, such projects depend on skilled and highly specialized manpower and the knowledge to motivate and develop them is an extremely important factor for achieving success in this area. Thus, this document sought to present a model of task allocation in software projects that considers, in addition to organizational goals (cost, time, etc.), the professional aspirations of the participating members. The proposed strategy for research is through the simulation of multi-agent systems, systems generally used for behavioral simulation entities. Through this model was intended to provide the manager a tool to aid in decision making in the process of task allocation in software development companies, allowing them to view different scenarios and strategies, looking for producing a better performance in project implementation and greater people satisfaction.